Peran Etika Kristen dalam Membentuk Sikap terhadap Praktik Aborsi di Indonesia dari Perspektif Teologi, Sosial dan Hukum - Saul Napat; Callista Anugrahni; Tirsa Tanzania; Sarmauli Sarmauli (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2025)
This study discusses the role of Christian ethics in shaping attitudes towards abortion in Indonesia, which has led to moral, social, and legal debates. The main issues examined are how the biblical view and Christian ethical teachings assess the act of abortion and how the attitude of the church and believers in responding to this phenomenon. The aim of this study is to understand theologically and ethically the position of the Christian faith on abortion, while offering a compassionate pastoral approach to women facing such moral dilemmas. The research method used is descriptive qualitative method, by examining various theological, social, and legal sources to describe in depth the views of Christian ethics on abortion. The results showed that in the view of Christian ethics, human life is a holy gift of God from the womb, so abortion is considered contrary to his will. However, the church and believers are called not only to reject abortion in a normative way, but also to provide mentoring, moral education, and spiritual support for those affected. This study confirms the importance of balance between truth and love in dealing with the issue of abortion as a concrete manifestation of the application of Christian ethics in society.